Phytochemical Composition and Antioxidant Properties of Dissotis erecta (Guill. & Perr.) Dandy Flowers - Ita, Basil Nse; Enin, Godwin Ndarake; Udo, Itoro Esiet (Sciences of Phytochemistry, 2025)
Dissotis erecta is a shrubby herb belonging to the Melastomataceae family, commonly found in Nigeria. It is widely recognized for its diverse ethnomedicinal applications, including treating edema, diarrhea, stomach discomfort, and rheumatism. Alongside other plant parts, its flowers, rich in biologically active compounds, are valued for their aesthetic appeal and potential health benefits. This study assessed the antioxidant properties, total phenolic, total flavonoid, and bioactive contents of the methanolic extract of D. erecta flowers. The antioxidant properties were determined by the DPPH radical scavenging activity, ABTS radical scavenging activity, ferric reducing activity, and metal chelating assay. The extract demonstrated strong DPPH radical scavenging activity, ABTS radical scavenging activity, metal chelating ability, and reducing power, with IC50 values of 79.84 ± 0.64 µg/mL, 125.77 ± 2.64 µg/mL, 87.89 ± 0.91 µg/mL, and 71.71 ± 0.55 µg/mL, respectively. Phytocompounds such as alkaloids, sterols, and terpenoids were present in the flower extract, while phlobatanins and glycosides were absent. Total phenolic content was 57.47 ± 0.21 mg GAE/g, while total flavonoid content was 83.52 ± 0.31 mg QE/g. Gas chromatography-mass spectroscopy (GC-MS) analysis identified α-terpineol (86.53%), nerolidol (7.44%), campesterol (1.12%), and neocurdione (1.29%) as the predominant components. These findings indicate that D. erecta flowers contain a significant amount of phytocompounds with antioxidative properties that could potentially be useful in managing diseases related to oxidative stress.